2003
DOI: 10.2307/4003830
|View full text |Cite
|
Sign up to set email alerts
|

Observations of Cattle Use of Prairie Dog Towns

Abstract: We investigated the use of prairie dog towns by cattle (Bos taurus) on the shortgrass steppe of northeastern Colorado by conducting surveys of cattle and vegetation from June to August 1999. Cattle presence and behavior were recorded 3 times a week during driving surveys of 15 black-tailed prairie dog (Cynomys ludovicianus) towns. A subset of 3 pastures with prairie dog towns was intensively surveyed twice weekly wherein the habitat and activity of a randomly chosen focal animal was recorded every 6 minutes fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 5 publications
0
18
2
Order By: Relevance
“…Vegetation canopy height is often reduced on black-tailed prairie dog towns (Archer et al 1987;Winter et al 2002), partly as a result of consumption and partly as a result of active clipping of the vegetation by prairie dogs allowing predator scanning (Hoogland 1995). Average canopy height was lower on (10 cm) than off (20 cm) black-tailed prairie dog towns in the mixed grass prairie (Archer et al 1987) and in the shortgrass steppe, where canopy height was about 6 cm on prairie dog towns and 12 cm off towns (Guenther and Detling 2003). However, we found no significant difference in canopy height on and off of Gunnison's prairie dog towns.…”
Section: Canopy Heightcontrasting
confidence: 53%
See 1 more Smart Citation
“…Vegetation canopy height is often reduced on black-tailed prairie dog towns (Archer et al 1987;Winter et al 2002), partly as a result of consumption and partly as a result of active clipping of the vegetation by prairie dogs allowing predator scanning (Hoogland 1995). Average canopy height was lower on (10 cm) than off (20 cm) black-tailed prairie dog towns in the mixed grass prairie (Archer et al 1987) and in the shortgrass steppe, where canopy height was about 6 cm on prairie dog towns and 12 cm off towns (Guenther and Detling 2003). However, we found no significant difference in canopy height on and off of Gunnison's prairie dog towns.…”
Section: Canopy Heightcontrasting
confidence: 53%
“…Plant species composition on black-tailed prairie dog towns generally shifts over time from grasses to forbs in northern mixed grass (Coppock et al 1983;Archer et al 1987;Whicker and Detling 1988) and shortgrass prairies (Winter et al 2002). Grazing by black-tailed prairie dogs also leads to increases in bare ground (Coppock et al 1983) and lower canopy height (Archer et al 1987;Winter et al 2002;Guenther and Detling 2003). These alterations and their subsequent influences on associated species have led to prairie dogs being characterized as a keystone species in many grasslands of western North America (Miller et al 1994;Kotliar et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…These predictions are consistent with Hobbs et al (1996a), who found that cattle grazing pastures with ,45 g/m 2 experienced significant reduction in DIR compared to cattle grazing pastures .45 g/m 2 . If cattle forage on colonies in proportion to their abundance (Guenther and Detling 2003), reduced DIR could only be offset by the 12% increase in digestibility for smaller cattle (e.g., 350-550 kg) that are able to attain IIR as high as that reported by Bergman et al (2000). In most cases, the net effect of prairie dogs is reduced daily nutrient intake and reduced cattle mass gain, the magnitude of which will increase with increased prairie dog abundance (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…We should not extrapolate this example from southwestern grasslands across the prairie dog's range. In short-grass steppe habitat in northeastern Colorado, USA, cows showed no preference for grazing on or off colonies (Guenther andDetling 2003, Detling 2006). In a northern mixed-prairie, bison showed a decided preference for grazing on prairie dog colonies (Coppock et al 1983b, Detling 2006.…”
Section: Competition Between Prairie Dogs and Large Ungulates Ecologimentioning
confidence: 99%